Civil Resistance and Student Activism in the Political Struggles of Bangladesh (1947-1971) (Journal of the Asiatic Society of Bangladesh, Humanities, 2025)
The political history of Bangladesh has been significantly shaped by student-led campaigns of civil resistance, understood as political action relying on nonviolent methods and tactics. In the long struggle for independent Bangladesh, civilians from diverse sections of the society embraced nonviolence as a strategy to challenge oppression and injustice. Yet, the account of nonviolent struggles has received less treatment in the literature. This paper is an attempt to analyze students’ nonviolent movement activism in Bangladesh from historical perspectives. In the events of civilian struggle in pre-independence Bangladesh (1947-1971), student activism became catalytic in forwarding popular demands, including establishing Bangla as the mother language, autonomy and self-rule, and independence. This paper investigates to what extent students as social actors could help mobilize broad-based civil resistance in the context of contention between power holders and civilian protesters. The analysis is informed by theoretical insights from resistance and protest movement studies. In this vein, this paper engages the political process approach to examine student-led civil resistance in the political history of Bangladesh. The data source includes published articles and books. Based on an extensive review of the secondary sources, the findings suggest that students’ strategic choice of nonviolent political action generated great appeal among ordinary civilians. It helped transform ordinary people’s power into social power which ultimately formed a base of mass resistance and helped to bring about significant socio-political changes in the political landscape of pre-independence Bangladesh.JASBH, Vol. 70(1), June 2025, pp. 89-108